As conexões repressivas no Cone Sul (1960-1990): Terrorismo de Estado em conexão internacional - Silva, Jussaramar da (2017)
This thesis deals with the repressive connections in the Southern Cone between the 1960s and 1990s, looking at how these countries have transformed their security systems into what can be called a singular repressive system, based on the articulation between agents and unity in Modus operandi adopted among various nations of this sub-continent, creating the practice of State Terror. Such connection merged the Counterrevolutionary War Doctrine with the National Security Doctrines, both practiced by external orientation, either French, or North American; Creating an International System of Repression. The strategies and tactics adopted in the persecutory actions against the "internal enemy" prove this connection; Demonstrating the financing of National States with this practice through the creation of training centers in order to standardize such actions or with the involvement of military attachés, whose most terrifying face is evident in the extermination practices, torture and extrajudicial actions that involved The official armed forces or their illegal arms, such as paramilitaries and death squads